Two new hyphomycetes from Indian sub-continent - and KAMAL*, R. KUMAR, A.N. RAI (Indian Phytopathology, 2002)
During routine frequent survey of the forest flora for the study of phytoparasitic fungi, two interesting foliicolous hyphomycetes were collected which upon detailed taxonomic treatment and observations proved to be new viz., Eriocercosporella indica gen. et sp. nov., Gonatophragmiella didymospora gen et sp. novo occurring on Marsiline roylae (Asclepiadaceae) and Croton roxburghii (Euphorbiaceae) respectively.